Assessment of osteoporotic fracture risk in patients with chronic obstructive pulmonary disease (Research, Society and Development, 2021)
Objective: To evaluate the risk of osteoporotic fracture and the indication of treatment for osteoporosis in patients with Chronic Obstructive Pulmonary Disease (COPD) through FRAX and NOGG. Methods: Descriptive, observational and cross-sectional study with a convenience sample carried out in a charity hospital in the city of Aracaju-SE. COPD patients were selected for the study and paired with healthy individuals. Results: The study sample consisted of 174 individuals, 87 in the COPD group (DG) and 87 in the control group (CG). Through clinical FRAX for absolute risk of major osteoporotic fracture for all study volunteers, 3 (3.44%) of the DG had indicative treatment value for osteoporosis and no participant in the CG. For hip fractures, it was found that 36 (41.4%) in the GD and 12 (13.8%) volunteers in the CG would have an indication for treatment. Through the NOGG methodology, 44 (50.6%) of the patients in the GD and 4 (4.6%) of the volunteers in the CG had an indication for treatment, 38 (43.7%) of the GD and 58 (66.6%) ) of the CG had an indication to perform bone densitometry. Conclusions: The data demonstrated that COPD increases the risk for osteoporotic fractures, especially in women and the elderly. Through NOGG it was possible to identify the risk of fracture with a higher positive and negative predictive value when compared to FRAX.